Identification of enuresis risk factors among primary school children in Makassar - Ratna Dewi Artati (Paediatrica Indonesiana, 2008)
Background Enuresis is a common problem among children andadolescents which may lead to important psychosocial distur-bances. Several factors have been associated with the occurrenceof enuresis, including genetic, family history and socioeconomiclevel. Not many population-based studies have been publishedrgarding this matter.Objectives To establish the prevalence of enuresis among schoolchildren and to identify the risk factors associated with thisdisorder.Methods A cross sectional population-based study was conductedfrom April to October 2007 in 600 children aged 6-14 years.Identification of enuresis risk factors were collected from studentsrandomly chosen from six primary schools located in differentregions ofMakassar. Data were collected via a questionnaire com-pleted by the parents. Study population were grade I to grade VIof primary school students in Makassar which were chosen fromhigh economic level schools group (SD I) and low economicallevel schools group (SD II).Results The overall prevalence of enuresis was 10.8%. Bivariateanalyses show relationships between the occurrence of enuresisand maternal and paternal educational level, family's socioeco-nomic status, family history of enuresis, and history of use of diaper.On logistic regression analysis, statistically significant relationshipswere found between enuresis and mother's educational level,family's socioeconomic status, family history of enuresis, andhistory of use of diaper.Conclusions Enuresis is a common problem among school childrenin Makassar and associated with several factors, including mother'seducational level, family socioeconomic status, family history ofenuresis and use of diaper